Titanium alloy, its manufacturing method and engine parts using the same
A bimodal structured titanium alloy with specific elemental compositions and microstructural control addresses the challenge of high-temperature strength and creep resistance, achieving enhanced mechanical properties for engine parts.
Patent Information
- Application Number
- JP2020151292
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-09
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-09-09
AI Technical Summary
Existing heat-resistant titanium alloys face challenges in maintaining high-temperature strength and creep resistance above 600°C, limiting their long-term use in high-temperature environments.
A titanium alloy with a bimodal structure composed of equiaxed α-Ti and layered α-Ti and β-Ti phases, containing specific elements like Al, Nb, Zr, Sn, Mo, and Si, is developed, with controlled microstructural features and manufacturing processes to enhance high-temperature strength and oxidation resistance.
The alloy exhibits excellent high-temperature strength and oxidation resistance, suitable for engine parts, with improved mechanical properties at temperatures up to 650°C, demonstrating strengths of 1250 MPa at room temperature, 800 MPa at 550°C, and 550 MPa at 650°C.
Smart Images

Figure 0007599685000004 
Figure 0007599685000005 
Figure 0007599685000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat-resistant titanium alloy exhibiting excellent high-temperature strength, a method for producing the same, and an engine part using the same. [Background technology]
[0002] Titanium alloys have been rapidly developed as structural materials over the past 60 years because they have excellent corrosion resistance and high specific strength among alloys. In recent years, there has been a demand for more efficient means of transportation through weight reduction, and there is an increasing demand for lighter and more efficient structural materials. Therefore, in the aircraft field, there is a need to install lighter and more powerful materials in the engines in order to reduce the weight of the aircraft engines and reduce fuel consumption, and titanium alloys are used for the disks and blades of aircraft engine compressors.
[0003] So far, heat-resistant titanium alloys have been developed mainly in the UK, USA, Russia, and China, and are essential structural materials for important components such as the inside of aircraft engines and airframes that are exposed to high temperatures below 600°C. Conventionally, heat-resistant titanium alloys used in aircraft engines include Ti-6242 (Ti-6Al-2Sn-4Zr-2Mo-0.1Si, mass%), Ti-1100 (Ti-6Al-2.8Sn-4Zr-0.4Mo-0.45Si), and TIMETAL 834 (Ti-5.8Al-4Sn-3.5Zr-0.3Mo-1Nb-0.3Si-0.06C). However, these alloys also undergo oxidation and creep deformation at temperatures above 600°C, and cannot withstand long-term use, so there is a demand for the development of titanium alloys that can stably withstand long-term use at temperatures above 600°C.
[0004] Patent Document 1 discloses an alloy containing, by mass%, 6.0-8.0% Al, 1.0-3.0% Mo, 0.05-3.0% Si, 0.08-0.25% C, and the balance being Ti and unavoidable impurities, as a heat-resistant titanium alloy having good hot workability, excellent high-temperature strength and high-temperature creep properties, and excellent scale spalling resistance at high temperatures. An alloy composition was found in which the strain after 100 hours at 760°C under 28 MPa is 2% or less, and the oxide film does not peel off after 100 hours in a 750°C oxidation test. However, in this case, the actual extent to which oxidation has progressed is not shown, and if the oxide film does not peel off even when oxidation progresses and a thick oxide film is formed, it may be evaluated as having excellent oxidation resistance.
[0005] Patent Document 2 discloses an alloy that can be manufactured into a thin plate by cold rolling and has sufficient high-temperature oxidation resistance and workability, and that is composed of, by mass%, Zr: 0.1 to 5.0%, Nb: 0.1 to 5.0%, Fe: 0.1% or less, oxygen: 0.1% or less, the balance being Ti and impurities. These alloys have good cold workability and an oxidation weight gain at 600°C of 0.5 mg / cm. 2 However, there is no mention of creep properties, and it is not possible to judge whether or not the high-temperature mechanical properties are excellent.
[0006] Patent Document 3 discloses an alloy containing, by mass%, 5 to 10% Al, 0.1 to 10% at least one of Sn and Zr, 0.1 to 5% at least one of Mo and V, 0.01 to 5% Sc, and O in a molar ratio with Sc of Sc:O=2:3 or less, with the remainder being Ti and unavoidable impurities, as a heat-resistant titanium alloy with high strength and excellent room temperature ductility that can be used at high temperatures. Patent Document 3 reports that the alloy has an excellent balance between room temperature ductility and high temperature strength by using an α phase, which has excellent high temperature strength due to solid solution strengthening, as the main component, and further strengthening with Sc2O3 and α2-Ti3Al compounds, and introducing 5% or less of a β phase, which has excellent workability. However, since creep properties are not mentioned, it is unclear whether the creep properties are excellent.
[0007] Patent Document 4 describes a titanium alloy with excellent oxidation resistance, which contains 0.1-12% by mass of Al, 0-7% by mass of Sn, 0.1-10% by mass of Ga, 0.1-7% by mass of Zr, 0-5% by mass of Mo, 0-4% by mass of W, 0-3% by mass of Nb, and 0.1-10% by mass of Ta. Patent Document 4 discloses alloys having a composition containing 0-4 mass% of Mn, 0-2 mass% of Si, and the remainder being composed of Ti and unavoidable impurities. In particular, referring to Table 1 of Patent Document 4, it is reported that the alloys of Examples 1 to 3, which satisfy the above composition and contain no Sn but no Ga, have superior oxidation resistance at a test temperature of 750°C compared to the alloys of Comparative Alloys 1 and 2, which contain Sn but no Ga.
[0008] Furthermore, Patent Document 4 discloses that the titanium alloy satisfying the above composition may contain any of the following elements alone or in combination: V: 4 mass% or less, Hf: 2 mass% or less, Cu: 1 mass% or less, B+C: 0.2 mass% or less, Y: 0.2 mass% or less, La: 0.2 mass% or less, and Ce: 0.2 mass% or less. Here, in an oxidation test at 750°C, a weight gain of 2 mg / cm after 240 hours is disclosed. 2 However, the creep strength is not disclosed, so it is not possible to judge whether the creep properties are excellent or not. In addition, the proposed alloy contains Ga and W, which are difficult to melt. W in particular is an element that is prohibited from being brought into manufacturing sites because it generates inclusions during melting.
[0009] Patent Document 5 discloses an alloy containing, by mass%, Al: 5% to 8%, Nb: 1% to 10%, Zr: 1% to 8%, Mo: 0% to 8%, Sn: 0% to 2%, and Si: 0% to 1%, with the remainder being Ti and unavoidable impurities, as a titanium alloy with a good balance between oxidation resistance and creep properties. The oxidation resistance at 750°C is superior to that of the commercial alloy TIMETAL834, but no comparison is made regarding creep properties, making it impossible to determine whether the creep properties are superior to those of TIMETAL834.
[0010] Non-Patent Document 1 reports the effect of adding Ga and Sn to an alloy of related composition (near α-type titanium alloy). In detail, the creep properties of a sample having a bimodal structure formed of an equiaxed α phase and a two-phase lamellar structure of α and β phases at 600°C and 310 MPa are shown, and the creep life is 22 hours for an alloy to which only Ga is added, 27 hours for an alloy to which Ga and Sn are simultaneously added, and 45 hours for an alloy to which only Sn is added, indicating that the addition of Sn is essential for improving creep properties.
[0011] Non-Patent Document 2 shows the strength and creep properties of the equiaxed structure of Ti-5.7Al-3.9Nb-3.8Zr-0.3Si alloy in mass %. It is reported that the strength at 600℃ is 270MPa, the fracture life at 550℃ under 240MPa is 236 hours, and the fracture life at 600℃ under 137MPa is 257 hours.
[0012] Non-Patent Document 3 shows the creep properties of a bimodal structure consisting of an equiaxed α phase and an α / β layered structure of a Ti-7.5Al-3.9Nb-3.8Zr alloy at 600°C and 137 MPa, and reports that the creep life is 2492 hours. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2006-283062 A [Patent Document 2] JP 2013-087306 A [Patent Document 3] JP 2012-251219 A [Patent Document 4] JP 2014-208873 A [Patent Document 5] JP 2020-026568 A [Non-patent literature]
[0014] [Non-Patent Document 1] T. Kitashima, Y. Yamabe-Mitarai, S. Iwasaki, S. Kuroda, Metall. Mater. Trans. A, 47A, (2016) 6394-6403 [Non-Patent Document 2] K. Shimagami, T. Ito, Y. Toda, A. Yumoto, Y. Yamabe-Mitarai, Mater. Sci. Eng. A, 756(2019)46-53. [Non-Patent Document 3] H. Masuyama, K. Shimagami, Y. Toda, T. Matsunaga, T. Ito, M. Shimojyo, Y. Yamabe-Mitarai, Mater. Trans., 60, 11(2019)2236-2345. Summary of the Invention [Problem to be solved by the invention]
[0015] An object of the present invention is to provide a heat-resistant titanium alloy exhibiting excellent high-temperature strength, a method for producing the same, and an engine part using the same. [Means for solving the problem]
[0016] [1] The titanium alloy of the present invention contains, by mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 1%, and C: 0.01% to 0.2%, with the remainder being Ti and unavoidable impurities. The titanium alloy has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated. [2] The titanium alloy of the present invention contains, by mass%, Al: 5% to 8%, Nb: 1% to 3%, Zr: 1% to 8%, Sn: 0.3% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 0.9%, and C: 0.01% to 0.15%, with the remainder being Ti and unavoidable impurities. The titanium alloy has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated. [3] The titanium alloy of the present invention contains, by mass%, Al: 6% to 7.5%, Nb: 1% to 2.5%, Zr: 1.5% to 6%, Sn: 1% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 3.5%, Si: 0.1% to 0.6%, and C: 0.01% to 0.1%, with the remainder being Ti and unavoidable impurities. The titanium alloy has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated. [4] The titanium alloy of the present invention contains, by mass%, Al: 6% to 7.5%, Nb: 1% to 2.5%, Zr: 3.6% to 5%, Sn: 4.1% to 5.5%, Mo: 0.5% to 3.5%, Si: 0.1% to 0.6%, and C: 0.01% to 0.1%, with the remainder being Ti and unavoidable impurities. The titanium alloy has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated.
[0017] [5] In the titanium alloy of the present invention, the volume fraction of the equiaxed α-Ti phase is preferably 40% or less. [6] In the titanium alloy of the present invention, the grain size of the equiaxed α-Ti phase is preferably in the range of 1 μm to 50 μm, and the thickness of the α phase within the lamellar structure is preferably in the range of 50 nm to 1 μm. [7] In the titanium alloy of the present invention, the grain size of the equiaxed α-Ti phase is preferably in the range of 5 μm to 30 μm, and the thickness of the α phase within the lamellar structure is preferably in the range of 100 nm to 1 μm. [8] In the titanium alloys [1] to [7] of the present invention, it is preferable that the alloy further contains an α2-Ti3Al phase. [9] In the titanium alloys [1] to [7] of the present invention, it is preferable that a silicide phase is further contained.
[10] In the titanium alloy of the present invention, preferably, the strain rate is 3x10 at room temperature, 550°C, and 650°C. -4 When subjected to a compression test at 2000 rpm / s, the strength is preferably 1250 MPa or more at room temperature, 800 MPa or more at 550°C, and 550 MPa or more at 650°C.
[0018]
[11] The method for producing a titanium alloy of the present invention includes the steps of melting an ingot containing, by mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 1%, and C: 0.01% to 0.2%, with the balance being Ti and unavoidable impurities; solution treating the ingot at a temperature in the α + β2 phase region; forging and / or rolling the solution-treated ingot at a temperature in the α + β2 phase region; heat treating the forged and / or rolled material at a temperature in the α + β phase region; and cooling the heat-treated material to room temperature at a cooling rate in the range of 1 °C / s to 30 °C / s.
[0019]
[12] In the method for producing a titanium alloy of the present invention, the heat treatment is preferably performed at a temperature range of more than 800°C and less than or equal to 1100°C.
[13] In the method for producing a titanium alloy of the present invention, the heat treatment is preferably performed for a period of time ranging from 30 minutes to 10 hours.
[14] In the method for producing a titanium alloy of the present invention, the cooling step preferably comprises cooling the processed material at a cooling rate in the range of 1° C. / sec to 30° C. / sec.
[15] In the method for producing a titanium alloy of the present invention, preferably, the method further comprises performing an aging treatment following the cooling.
[16] In the method for producing a titanium alloy of the present invention, the aging treatment is preferably performed by aging the processed material at a temperature range of 300°C or more and 800°C or less for a time period of 30 minutes or more and 10 hours or less.
[17] In the method for producing a titanium alloy of the present invention, preferably, the method further comprises water cooling following the aging treatment.
[0020]
[18] The titanium alloy of the present invention may be used for engine components. Effect of the Invention
[0021] The titanium alloy of the present invention contains, by mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, and Si: 0.1% to 1%, with the balance being Ti and inevitable impurities. All of these elements except Sn improve the oxidation resistance, so the oxidation resistance is excellent. Furthermore, the titanium alloy of the present invention forms a bimodal structure consisting of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked. The titanium alloy of the present invention has excellent high-temperature strength due to this unique structure, and is suitable for engine parts.
[0022] The method for producing the titanium alloy of the present invention includes the steps of melting an ingot of a material satisfying the above-mentioned composition by a melting method, solution treating it at a temperature in the α+β2 phase region, forging and / or rolling it at a temperature in the α+β2 phase region, heat treating the forged and / or rolled processed material at a temperature in the α+β phase region, and cooling it to room temperature at a cooling rate in the range of 1°C / sec to 30°C / sec. The above-mentioned unique structure is formed by controlling the heat treatment temperature to the temperature in the α+β phase region and the cooling rate to 30°C / sec or less. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a flow chart showing the manufacturing process of the titanium alloy of the present invention. [Figure 2A] FIG. 2(a) is an SEM image showing the structure of the sample of Example 1. [Figure 2B] FIG. 2(b) is an SEM image showing the structure of the sample of Example 2. [Figure 2C] FIG. 2(c) is an SEM image showing the structure of the sample of Example 3. [Figure 2D] FIG. 2(d) is an SEM image showing the structure of the sample of Example 4. [Figure 2E] FIG. 2( e ) is an SEM image showing the structure of the sample of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The present inventors have focused on titanium alloys containing elements that improve the oxidation resistance of the alloys, and have succeeded in strengthening the alloys through the composition of the titanium alloys and improving their high-temperature strength.
[0025] The titanium alloy of the present invention contains aluminum (Al): 5% to 8%, niobium (Nb): 1% to 3.5%, zirconium (Zr): 1% to 8%, tin (Sn): 0% to 10%, Sn + Zr: 4% to 12%, molybdenum (Mo): 0.5% to 4%, silicon (Si): 0.1% to 1%, and carbon (C): 0.01% to 0.2%, with the balance being titanium (Ti) and inevitable impurities. Examples of inevitable impurities include nitrogen (N), yttrium (Y), boron (B), magnesium (Mg), chlorine (Cl), copper (Cu), and hydrogen (H), which are inevitable impurities contained in raw materials. The structure of the titanium alloy of the present invention has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked. Such a structure can strengthen the alloy and improve its high-temperature strength.
[0026] Al: Al improves oxidation resistance and stabilizes the equiaxed α-Ti phase. If it is 5% by mass or more, it can strengthen the equiaxed α-Ti phase through solid solution. Furthermore, the α2-Ti3Al phase precipitates, and creep properties are expected to improve. If it is 8% by mass or less, it suppresses the precipitation of brittle compounds such as Ti3Al, and provides excellent workability. Preferably, Al is in the range of 6% by mass or more and 7.5% by mass or less.
[0027] Nb: Nb improves oxidation resistance. If it is 1 mass% or more, it is advantageous for improving oxidation resistance. If it exceeds 3.5 mass%, silicide may be difficult to precipitate in the β-Ti phase. Nb is preferably in the range of 1 mass% or more and 3 mass% or less. More preferably, Nb is in the range of 1 mass% or more and 2.5 mass% or less.
[0028] Zr: Zr improves oxidation resistance and stabilizes and strengthens the equiaxed α-Ti phase. If it is 1% by mass or more, it improves oxidation resistance and is advantageous for stabilizing and strengthening the equiaxed α-Ti phase. If it is 8% by mass or less, it is excellent in oxidation resistance and workability. If it exceeds 8% by mass, there is a risk of the workability being deteriorated. Preferably, Zr is in the range of 1.5% by mass or more and 6% by mass or less.
[0029] Sn: Sn is not essential, but is preferred because it stabilizes and strengthens the equiaxed α-Ti phase. If it is 10 mass% or less, it is advantageous for stabilizing and strengthening the equiaxed α-Ti phase. Although Sn may reduce the oxidation resistance, adding it together with Zr reduces the reduction in oxidation resistance. For this reason, when adding Sn, Zr is essential, and Sn + Zr must be 4 mass% or more. If it is 12 mass% or more, workability is deteriorated.
[0030] Mo: Mo is necessary to improve oxidation resistance and to strengthen the β-Ti phase. If it is 0.5 mass% or more, it is advantageous to strengthen the β-Ti phase. If it exceeds 4 mass%, there is a risk of destabilizing the α-Ti phase. Preferably, Mo is in the range of 0.5 mass% or more and 3.5 mass% or less.
[0031] Si: Si is necessary for silicide precipitation. For this reason, if it is 1 mass% or less, it is advantageous for improving oxidation resistance, strengthening the equiaxed α-Ti phase, and strengthening by silicide precipitation. If it exceeds 1 mass%, coarse silicide is generated and is not effective for strengthening. Preferably, Si is in the range of 0.1 mass% to 0.9 mass%. More preferably, Si is in the range of 0.1 mass% to 0.6 mass%. The silicide is a Ti5Si3 phase, which strengthens the titanium alloy.
[0032] C: C is necessary to stabilize and strengthen the equiaxed α-Ti phase. For this reason, if the C content is 0.2 mass% or less, it is advantageous for strengthening the α-Ti phase. If the C content exceeds 1 mass%, carbon cannot be dissolved in the α-Ti phase, and carbides are generated, resulting in embrittlement. Preferably, C is in the range of 0.01 mass% or more and 0.15 mass% or less. More preferably, C is in the range of 0.01 mass% or more and 0.1 mass% or less.
[0033] The compositional combination of each element can be arbitrarily selected from the above-mentioned ranges, but examples include the above-mentioned compositions [1] to [4]. The titanium alloy of the present invention has a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked, but the volume fraction of the equiaxed α-Ti phase is 40% or less. As a result, the titanium alloy of the present invention exhibits excellent high-temperature strength. Preferably, the equiaxed α-Ti phase satisfies a range of 0.5% to 20% by volume with respect to the layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked. As a result, the titanium alloy of the present invention exhibits excellent high-temperature strength. More preferably, the equiaxed α-Ti phase satisfies a range of 0.5% to 15% by volume, more preferably a range of 1% to 15% by volume with respect to the layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked. The ratio of the equiaxed α-Ti phase and the layered structure in which the α-Ti phase and the β-Ti phase are alternately stacked can be calculated by image diagnosis by microscope observation such as a scanning electron microscope.
[0034] In the titanium alloy of the present invention, the grain size of the equiaxed α-Ti phase is in the range of 1 μm to 50 μm, and the thickness of the α-Ti phase in the lamellar structure is in the range of 50 nm to 1 μm. This allows the titanium alloy of the present invention to exhibit excellent high-temperature strength. More preferably, the grain size of the equiaxed α-Ti phase is in the range of 5 μm to 30 μm, and the thickness of the α-Ti phase in the lamellar structure is in the range of 100 nm to 1 μm. The grain size of the equiaxed α-Ti phase and the thickness of the α-Ti phase in the lamellar structure can be measured for multiple structures in an image observed by a microscope such as a scanning electron microscope, and the average can be calculated.
[0035] As described above, the titanium alloy of the present invention has excellent high-temperature strength, and therefore can be used for aircraft engine parts such as compressor blades and compressor disks, turbine parts for thermal power plants, and heat-resistant parts for internal combustion engines.
[0036] FIG. 1 is a flow chart showing the manufacturing process of the titanium alloy of the present invention. Step S110: A material containing, in mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn+Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 1%, and C: 0.01% to 0.2%, with the balance being Ti and unavoidable impurities, is melted to produce an ingot. As long as the material satisfies the above-mentioned composition, it may be a simple metal such as sponge titanium, an alloy, or a compound. The composition of the above-mentioned material may be selected in the same manner as the composition of the titanium alloy of the present invention. Any melting method may be used, and examples of the melting method include arc melting, electron beam melting, and high-frequency melting.
[0037] Step S120: The ingot obtained in step S110 is solution-treated at a temperature in the α+β2 phase region. This allows the additive elements to dissolve in solid solution. Preferably, the ingot is solution-treated at a temperature range of 800°C to 1100°C. The time for the solution treatment is not particularly limited, but is illustratively 30 minutes to 24 hours.
[0038] Step S130: The solution-treated ingot obtained in step S120 is forged and / or rolled at a temperature in the α+β2 phase region. Hereinafter, the material that has been forged and / or rolled is referred to as the processed material.
[0039] In the forging and / or rolling, the ingot is preferably forged and / or rolled at a temperature range of 800°C to 1100°C so that the deformation amount is 50% or more. There is no particular upper limit, but for example, the deformation amount may be 100% or less. There are no particular limitations on the forging and rolling, but for example, hot forging, cold forging, hydraulic forging, etc. can be used for forging, and grooved rolling, strain rate controlled rolling, cold rolling, etc. can be used for rolling.
[0040] Step S140: The processed material forged and / or rolled in step S130 is heat-treated at a temperature in the α+β phase region. As a result, the α phase and the β phase grow with the strain and dislocations introduced by the processing as the driving force. The time of the heat treatment is not particularly limited, but is illustratively 30 minutes to 10 hours. Any furnace such as an atmosphere furnace, an electric furnace, or a tubular furnace may be used for the heat treatment.
[0041] Step S150: The processed material after the heat treatment obtained in step S140 is cooled to room temperature at a cooling rate in the range of 1°C / sec to 30°C / sec. By cooling at a cooling rate in this range, the α phase is generated in the β phase in a plate-like shape, forming a layered structure. Preferably, the processed material is cooled at a cooling rate in the range of 2°C / sec to 25°C / sec, more preferably 5°C / sec to 20°C / sec. This range promotes the formation of the above-mentioned structure. The atmosphere for the heat treatment is air, an inert gas, a vacuum, or the like.
[0042] Although not shown, aging treatment is performed following step S150. Specifically, the processed material (or the titanium alloy of the present invention) obtained in step S150 is aged for 30 minutes to 10 hours at a temperature range of 300°C to 800°C. This promotes the precipitation of silicide (e.g., Ti5Si3 phase) in the layered structure in which the α2-Ti3Al phase and the α-Ti phase and the β-Ti phase are alternately stacked in the equiaxed α-Ti phase, which can further strengthen the material. After the aging treatment, water cooling (cooling rate of >100°C / sec) may be performed.
[0043] The present invention will now be described in detail with reference to specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES
[0044] [Example 1 to Example 5] The samples of Examples 1 to 5 were prepared as follows. Sponge Ti, Al pellets, Nb granular raw material, Zr granular raw material, Sn granular raw material, Mo granular raw material, Si granular raw material, and TiC granular raw material were weighed so as to satisfy the composition of Table 1, and melted by high-frequency melting to produce an ingot (step S110 in FIG. 1). Next, the obtained ingot was solution treated at 1000°C for 30 minutes (step S120 in FIG. 1). After that, the solution-treated ingot was forged and grooved rolled at 1000°C (step S130 in FIG. 1). In this way, a rod-shaped processed material having a size of 15 mm square was obtained. The processed material was heat treated in air at the heat treatment temperature shown in Table 1 for 3 hours (step S140 in FIG. 1). Next, the processed material after the heat treatment was cooled to room temperature at the cooling rate shown in Table 1 (step S150 in FIG. 1). After cooling, the specimen was aged at 650°C for 5 hours and then water-cooled. The cooling rate of the water-cooling was much faster than 100°C / sec.
[0045] [Table 1]
[0046] The compositions of the samples of Examples 1 to 5 were confirmed by elemental analysis using an energy dispersive X-ray spectrometer (EDS) attached to a scanning electron microscope (SEM), and were found to be as shown in Table 1. The samples of Examples 1 to 4 were observed using the SEM. The observation results are shown in FIG.
[0047] FIG. 2 is a set of SEM images showing the structures of the samples of (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, and (e) Example 5.
[0048] According to FIG. 2(a), the sample of Example 1 had a bimodal structure composed of an equiaxed α-Ti phase, an α-Ti phase, and a β-Ti phase, which are alternately stacked, as shown by the black contrast. The grain size of the equiaxed α-Ti phase was 10 μm, and the amount was 10%. The width of the α phase in the layered structure was 1 μm or less. According to FIG. 2(b), the sample of Example 2 had a bimodal structure composed of an equiaxed α-Ti phase, an α-Ti phase, and a β-Ti phase, which are alternately stacked, as shown by the black contrast. The grain size of the equiaxed α-Ti phase was 8 μm, and the amount was 3%. The width of the α phase in the layered structure was 1 μm or less. According to FIG. 2(c), the sample of Example 3 had a bimodal structure composed of an equiaxed α-Ti phase, an α-Ti phase, and a β-Ti phase, which are alternately stacked, as shown by the black contrast. The grain size of the equiaxed α-Ti phase was 10 μm, and the amount was 15%. The width of the α phase in the layered structure was 1 μm or less. The fine white granular matter was silicide. According to Fig. 2(d), the sample of Example 4 had a bimodal structure consisting of a layered structure in which the equiaxed α-Ti phase, the α-Ti phase, and the β-Ti phase were alternately stacked. The grain size of the equiaxed α-Ti phase was 5 μm, and the amount was 40%. The width of the α phase in the layered structure was too fine to be observed in the SEM image. According to Fig. 2(e), the sample of Example 5 had a bimodal structure consisting of a layered structure in which the equiaxed α-Ti phase, the α-Ti phase, and the β-Ti phase were alternately stacked, as shown by the black contrast. The grain size of the equiaxed α-Ti phase was 10 μm, and the amount was 10%. The width of the α phase in the layered structure was 1 μm or less.
[0049] From the above results, it was shown that a titanium alloy having a bimodal structure composed of a layered structure in which equiaxed α-Ti phase, α-Ti phase, and β-Ti phase are alternately laminated was obtained by the manufacturing process shown in Figure 1, which contains, by mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 1%, and C: 0.01% to 0.2%, with the remainder being Ti and unavoidable impurities. In particular, it was shown that a combination of a heat treatment at a temperature in the α + β phase region (here, a temperature range of more than 800 ° C. and less than 1100 ° C.) that satisfies the above composition and a cooling rate in the range of 1 ° C. / sec to 30 ° C. / sec is effective.
[0050] Next, compression tests were performed on the samples of Examples 1 to 5 at room temperature, 550°C, and 650°C at a constant crosshead speed of 0.1 mm / min. In the compression tests at room temperature, the samples were clamped between jigs and deformed at a speed of 0.1 mm / min. In the tests at 550°C and 650°C, the temperature of the furnace attached to the testing machine was raised to the test temperature, the samples were inserted, and the sample temperature was held for 30 minutes until it reached the test temperature, after which deformation was performed at a speed of 0.1 mm / min. The results are shown in Table 2.
[0051] [Table 2]
[0052] According to Table 2, in comparison with Example 5 which is a commercial alloy, Examples 2 to 4 have higher strength at room temperature, and at 550°C and 650°C they also have the same or higher strength.
[0053] Next, an oxidation test was carried out for up to 500 hours at 650° C. for the samples of Examples 1 to 5. The weight increase due to the formation of an oxide film during the oxidation test was measured. Table 3 shows the weight increase after 500 hours.
[0054] [Table 3]
[0055] According to Table 3, the oxidation weight gain of Examples 3 and 4 was comparable to that of the commercial alloys. The high temperature strength in Table 2 and the oxidation test in Table 3 show that the compositions of Examples 3 and 4 have strengths comparable to or higher than those of the commercial alloys.
[0056] From the above results, it has been shown that a titanium alloy containing, by mass%, Al: 5% to 8%, Nb: 1% to 3.5%, Zr: 1% to 8%, Sn: 0% to 10%, Sn + Zr: 4% to 12%, Mo: 0.5% to 4%, Si: 0.1% to 1%, and C: 0.01% to 0.2%, with the remainder being Ti and unavoidable impurities, and having a bimodal structure composed of a layered structure in which equiaxed α-Ti phase, α-Ti phase, and β-Ti phase are alternately laminated, is a material with excellent high-temperature strength at temperatures of 600°C or more, and is suitable for engine parts.
[0057] In particular, the titanium alloy of the elemental composition of Example 3 is a material excellent in high-temperature strength at temperatures of 600°C or higher. Therefore, taking into consideration the allowable error of ±0.5% to ±1.0% for industrial use, the elemental composition of Example 3 is preferably a titanium alloy containing, by mass%, Al: 6% to 7.5%, Nb: 1% to 2.5%, Zr: 3.6% to 5%, Sn: 4.1% to 5.5%, Mo: 0.5% to 3.5%, Si: 0.1% to 0.6%, and C: 0.01% to 0.1%, with the balance being Ti and unavoidable impurities, and having a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated. In this case, the strain rate of 3x10 at room temperature, 550°C, and 650°C is preferably 3x10 -4 When a compression test is performed at 1000 / s, the strength is 1250 MPa or more at room temperature, 800 MPa or more at 550°C, and 550 MPa or more at 650°C. When a measurement error of about 10% is taken into account in the measured values of Example 3, the upper limit of the strength when a compression test is performed is 1464 MPa or less at room temperature, 1045 MPa or less at 550°C, and 700 MPa or less at 650°C. Here, room temperature is 25°C. [Industrial Applicability]
[0058] The titanium alloy of the present invention has the above-mentioned composition and structure, and therefore has excellent oxidation resistance and high-temperature strength, and is therefore applicable to aircraft engine parts such as compressor blades and compressor disks, turbine parts for thermal power plants, and heat-resistant parts for internal combustion engines.
Claims
1. In mass percent, Al: 6% or more and 7.5% or less, Nb: 1% or more and 2.5% or less, Zr: 3.6% or more and 5% or less, Sn: 4.1% or more and 5.5% or less, Mo: 0.5% or more and 3.5% or less, Si: 0.1% or more and 0.6% or less, and C: 0.01% or more and 0.1% or less and the balance being Ti and unavoidable impurities, and having a bimodal structure composed of an equiaxed α-Ti phase and a layered structure in which the α-Ti phase and the β-Ti phase are alternately laminated.
2. 2. The titanium alloy according to claim 1, wherein the equiaxed α-Ti phase has a volume fraction of 40% or less.
3. The grain size of the equiaxed α-Ti phase is in the range of 1 μm to 50 μm, 3. The titanium alloy according to claim 1, wherein the thickness of the α phase in the lamellar structure is in the range of 50 nm to 1 μm.
4. The grain size of the equiaxed α-Ti phase is in the range of 5 μm to 30 μm, 3. The titanium alloy according to claim 1, wherein the thickness of the α phase in the lamellar structure is in the range of 100 nm to 1 μm.
5. α 2 -Ti 3 The titanium alloy according to any one of claims 1 to 4, further containing an Al phase.
6. The titanium alloy according to any one of claims 1 to 5, further comprising a silicide phase.
7. At room temperature, 550°C, and 650°C, the strain rate was 3x10 -4 The titanium alloy according to any one of claims 1 to 6, wherein the strength when subjected to a compression test at 1000 MPa / s is 1250 MPa or more at room temperature, 800 MPa or more at 550 ° C, and 550 MPa or more at 650 ° C.
8. producing an ingot by a melting method from a material containing, by mass%, Al: 6% to 7.5%, Nb: 1% to 2.5%, Zr: 3.6% to 5%, Sn: 4.1% to 5.5%, Mo: 0.5% to 3.5%, Si: 0.1% to 0.6%, and C: 0.01% to 0.1%, with the balance being Ti and unavoidable impurities; subjecting the ingot to a solution treatment in a temperature range of 800° C. or more and 1100° C. or less; forging and / or rolling the solution-treated ingot at a temperature in the range of 800° C. to 1100° C.; Heat treating the forged and / or rolled material in a temperature range of more than 800° C. and less than or equal to 1100° C.; The processed material after the heat treatment is cooled to room temperature at a cooling rate in the range of 1° C. / sec to 30° C. / sec. The method for producing a titanium alloy according to any one of claims 1 to 7, comprising:
9. 9. The method of claim 8, wherein said heat treating comprises heat treating said fabric material for a time period ranging from 30 minutes to 10 hours.
10. 10. The method of claim 8 or 9, wherein the cooling comprises cooling the workpiece at a cooling rate in the range of 1°C / sec to 30°C / sec.
11. The method of any of claims 8 to 10, further comprising an aging treatment following said cooling.
12. 12. The method of claim 11, wherein the aging comprises aging the fabricated material at a temperature in the range of 300°C to 800°C for a time period of 30 minutes to 10 hours.
13. 13. The method of claim 12, further comprising water quenching following said aging.
14. An engine part made of the titanium alloy according to any one of claims 1 to 7.
Citation Information
Patent Citations
Heat resistant titanium alloy excellent in high temperature fatigue strength
JP1997031572A
Heat-resistant titanium alloy, and engine valve formed using it
JP2006283062A
Heat resistant titanium alloy
JP2012251219A
Heat-resistant titanium alloy
JP2013087306A
High-strength titanium alloy having excellent oxidation resistance and compressor component using the same
JP2014208873A
